2016
DOI: 10.3390/nano6110195
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Controlled Fabrication of InN Nanowires on Brass Substrates

Abstract: Growth of semiconductor nanowires on cheap metal substrates could pave the way to the large-scale manufacture of low-cost nanowire-based devices. In this work, we demonstrated that high density InN nanowires can be directly grown on brass substrates by metal-organic chemical vapor deposition. It was found that Zn from the brass substrates is the key factor in the formation of nanowires by restricting the lateral growth of InN. The nanowire morphology is highly dependent on the growth temperature. While at a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…[21] In the case of group III-nitrides, GaN and (Al,Ga)N NWs were demonstrated on flexible Ti and Ta metal foils, [5,6] while InN NWs were reported on brass foil substrates. [22] On Ta foils, GaN NW-based LEDs have also been recently demonstrated. [6] In a previous work we found that the structural and optical quality of self-assembled GaN NW ensembles grown on a Ti foil are comparable to those of similar structures grown on Si.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] In the case of group III-nitrides, GaN and (Al,Ga)N NWs were demonstrated on flexible Ti and Ta metal foils, [5,6] while InN NWs were reported on brass foil substrates. [22] On Ta foils, GaN NW-based LEDs have also been recently demonstrated. [6] In a previous work we found that the structural and optical quality of self-assembled GaN NW ensembles grown on a Ti foil are comparable to those of similar structures grown on Si.…”
Section: Introductionmentioning
confidence: 99%
“…[5] For many applications, vertical NW ensembles are highly desirable or even required. However, for NWs grown on metal foils a broad distribution of tilt angles with respect to the substrate normal is commonly observed [6,17,22]. For the case of GaN NWs grown on foils of Ti and Ta, this phenomenon was attributed to an epitaxial relation between the NWs and the individual grains of the polycrystalline metal foil.…”
Section: Introductionmentioning
confidence: 99%
“…The realization of light-emitting devices on metal thin films and metal substrates has been considered as a viable solution. Various metals, such as Mo, brass, TiN, Ta, and Ti foils, have been used for nucleating NWs for devices that emit in the UV and visible wavelength ranges [9][10][11][12][13]. Moreover, thin films of metal on silicon, or metal foils, have been regarded as less expensive alternatives to bulk metal substrates, especially in realizing a roll-to-roll fabrication process [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, III-nitride NWs grown on pre-orienting thin film metal layer have been demonstrated. [2,3] However, the high thermal mismatch between metals, e.g. Ti, and Si, causes delamination of the Ti thin-film from the Si substrate when devices are operated at elevated injection current density, thus causing device failure.…”
Section: Introductionmentioning
confidence: 99%